Experiences and coping mechanisms during the quarantine period among the contacts of COVID-19 patients in India - Nitin Joseph; Shubhi Chaudhary; Rishi Das; Mohammed Hashim; Deepak Kumar; Anjali Murthy; Sheikh Moiz Abdullah; Isha Goyal (Elsevier, 2024)
Introduction: This cross-sectional study was done to determine participants' experiences and coping mechanisms during quarantine. Methods: Data were collected using a Microsoft form distributed among the general population of Mangalore city. Results: Of the 113 participants, 41(36.3%) were quarantined at a hostel or a hotel-turned-quarantine facility. Among them, 48.8% felt that the living conditions were average or poor. 55(48.7%) participants did not disinfect their frequently touched surfaces in the quarantine facility even once a day. 27(23.9%) participants were put under quarantine along with others. 71(62.8%) participants reported anxiety during the quarantine period, which was mainly regarding COVID-19 test results [43(60.6%)]. The information provided regarding preparations required for quarantine was reported as less than adequate by 52(46%) participants. Coping mechanisms were adopted by 64(56.6%) participants. Quality of care in the quarantine period was reported to be poor among 9(8%) participants. It was poor among those >20 years (p = 0.0394), and among female participants (p = 0.01). 43(38%) participants experienced behavioural changes in the post-quarantine period. 41(36.3%) participants lived in constant fear of re-exposure to COVID-19 after completing quarantine. 39(34.5%) participants experienced stigma at their place of work. The post-quarantine experience was unpleasant among 36(31.9%) participants. It was particularly more among those aged 21-30 years (p = 0.01), those from nuclear families (p = 0.042), and those belonging to upper SES (p = 0.0021). Conclusion: Several incorrect practices and adverse experiences were identified among participants during the quarantine and the post-quarantine period. Address of these issues, and further strengthening of coping mechanisms, is required among the quarantined population.